Two Decades of Digital Citizenship Research Trends: A Bibliometric Analysis of the Scopus Database (2004–2024) - Aprilianata, Aprilianata; Mahendra, Wisnu; Ramadhan, Idang (De Cive : Jurnal Penelitian Pendidikan Pancasila dan Kewarganegaraan, 2025)
Over the past few decades, digital citizenship has become an increasingly important subject of academic research. A person's ability to use digital technology effectively and responsibly in their daily lives is referred to as digital citizenship. To reduce the gap in access to technology, the public must participate in responding to the development of digital technology and the revival of internet use. The purpose of this study is to identify research trends on the subject of digital citizenship. This study used 215 documents searched in the Scopus database and used bibliometric analysis techniques with RStudio and VOSviewer. From the results of the analysis, it can be concluded that this study started from 2004 to 2024, with an increase of 24.19 percent in 2024. The devices with the highest h-index are Information Technology and Education. The most productive affiliates are The Ohio State University, University of North Carolina Charlotte, Near East University, University of Muhammadiyah Surakarta, and University of Missouri. Choi M discussed research on digital citizenship with the highest total citations. The words media literacy, digital citizenship education, teachers, and professional digital competence are recommended keywords used when you want to conduct research on the topic of digital citizenship.